A qualitative analysis of social enterprises as mechanisms for boosting agricultural productivity in Kenya - Mburu, Shirley Wanjiku (Research of GSB, 2018)
With the ever expanding role of social enterprises globally, this research aims to build awareness of the role that social enterprises play in the Kenyan agricultural sector and investigate the factors that influence the development of agricultural social enterprises in Kenya. The data analysed for this study was collected via semi-structured interviews as part of a wider study, 'A case study of health and agriculture social enterprises in Kenya', commissioned by the Overseas Development Institute (ODI) and implemented by the Bertha Centre for Social Innovation and Entrepreneurship at the University of Cape Town Graduate School of Business. The writer of this study was part of the team that collected and published the preceding ODI report from the data set now utilised in this study.